Warty Squamous Cell Carcinoma of Anogenital Region: A Case Report in an HIV-positive Patient - Deepthy Vijayaraghavan; Neha Betty Issac (GAIMS Journal of Medical Sciences)
Venereal infections significantly contribute to the development of anogenital cancers, and Human papillomavirus (HPV) is the most common sexually transmitted disease worldwide. Warty squamous cell carcinoma is an extremely rare aggressive variant that generally occurs in the severely immunosuppressed at sites like the anogenital and genito-urethral regions. Though its etiology is thought to be multifactorial, 95% cases are attributed to HPV infection. Of the various subtypes, the high-risk HPV serotypes, particularly HPV 16 and 18, are the main risk factors for warty carcinoma.